Direct Oral Anticoagulants Versus Vitamin K Antagonists After Mitral Valve Transcatheter Edge‐to‐Edge Repair in Patients With Atrial Fibrillation: A Single‐Center Observational Study - Jan‐Hendrik Schipper; Anne‐Sophie Sommer; Richard Julius Nies; Clemens Metze; Max Maria Meertens; Jonas Wörmann; Sebastian Dittrich; Jan‐Hendrik van den Bruck; Arian Sultan; Jakob Lüker; Daniel Steven; Christopher Hohmann; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Mitral valve transcatheter edge‐to‐edge repair (M‐TEER) has emerged as a viable therapy option in patients with severe mitral regurgitation and high surgical risk. Although atrial fibrillation is common among patients undergoing M‐TEER, the optimal anticoagulatory treatment after the intervention is unknown. Methods A single‐center retrospective observational analysis was conducted using data from the M‐TEER registry at the University Hospital Cologne collected from 2019 untill 2021 including patients undergoing M‐TEER between November 2012 and April 2019. Patients with atrial fibrillation receiving consistent anticoagulation following M‐TEER were categorized into a direct oral anticoagulant or a vitamin K antagonist (VKA) group. The primary end point was a composite of ischemic cerebrovascular and bleeding events. Additionally, overall survival was assessed. Results Among 613 patients undergoing M‐TEER, 206 met the inclusion criteria, with 61 receiving direct oral anticoagulants and 145 receiving VKAs. After a median follow‐up of 833 (interquartile range, 355–1271) days, the incidence of the composite primary end point did not differ between direct oral anticoagulant and VKA groups (hazard ratio [HR], 0.51 [95% CI, 0.23–1.12]; P=0.07). Similarly, rates of ischemic cerebrovascular events and bleeding events were similar between groups. However, the overall mortality rate was higher in the VKA group (HR, 2.56 [95% CI, 1.54–4.26]; P=0.002). In the multivariable analysis, oral anticoagulation with a VKA was an independent predictor for death (adjusted HR, 2.23 [95% CI, 1.08–5.06]; P=0.03). Conclusions Our findings suggest that direct oral anticoagulants may offer comparable efficacy and safety to VKAs in preventing thromboembolic events following M‐TEER in patients with atrial fibrillation. Further randomized trials are needed to confirm these results and establish optimal anticoagulation strategies in this patient population.